2014
DOI: 10.2147/cia.s67602
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aural stimulation with capsaicin ointment on swallowing function in elderly patients with non-obstructive dysphagia

Abstract: ObjectiveIn the present study, an attempt was made to examine the effects of aural stimulation with ointment containing capsaicin on swallowing function in order to develop a novel and safe treatment for non-obstructive dysphagia in elderly patients.DesignA prospective pilot, non-blinded, non-controlled study with case series evaluating a new treatment.SettingSecondary hospitals.Patients and methodsThe present study included 26 elderly patients with non-obstructive dysphagia. Ointment containing 0.025% capsaic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…TRPV1 is considered to be a therapeutic target of OD [21]. Capsaicin is a specific agonist to TRPV1, and it has occasionally been reported that administration of capsaicin improves OD [22,23,24,25]. However, there are no randomized, double-blind, placebo-controlled trials on the effect of capsaicin on OD to date.…”
Section: Introductionmentioning
confidence: 99%
“…TRPV1 is considered to be a therapeutic target of OD [21]. Capsaicin is a specific agonist to TRPV1, and it has occasionally been reported that administration of capsaicin improves OD [22,23,24,25]. However, there are no randomized, double-blind, placebo-controlled trials on the effect of capsaicin on OD to date.…”
Section: Introductionmentioning
confidence: 99%
“… 20 However, in our previous study, repeated alternative application with ointment containing 0.025% capsaicin to each external auditory canal once a day for 7 days still improved swallowing function in patients with dysphagia. 4 Therefore, once-a-day alternative application to each external auditory canal with low-dose capsaicin may be a useful method to prevent capsaicin defunctionalization, although it is still uncertain how long the effects of single application with capsaicin ointment last. Furthermore, multicenter studies are required to explore whether repeated aural stimulation with 0.025% capsaicin ointment in such a way to prevent capsaicin defunctionalization really reduces the incidence of aspiration pneumonia in patients with dysphagia.…”
Section: Discussionmentioning
confidence: 99%
“…As a subset of neurons in the vagal nodose ganglion expresses TRPV1, 6 our previous study suggested that ointment containing capsaicin activates TRPV1 in vagal Arnold’s nerve of the external auditory canal, resulting in improvement of the swallowing function. 4 However, we cannot exclude the possibility that a nonspecific mechanical stimulation of the external auditory canal with a cotton swab rather than the TRPV1-mediated stimulation with capsaicin improves swallowing function in dysphagic patients. To exclude this possibility, we designed a randomized, placebo-controlled, double-blind, comparative study to compare the effects of ointment containing capsaicin on swallowing function to those of placebo in elderly patients with dysphagia.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Application of a TRPV1 agonist into the ear canal can also improve swallowing performance [ 138 ]. A pilot study reported that acute or chronic (once daily for 7 days) application of capsaicin-containing ointment (around 1 mM) in the external auditory canal improved swallowing function in older patients with dysphagia, as assessed by endoscopic swallowing scores [ 138 ]. In this study, the effects lasted for 60 min after an acute application [ 138 ].…”
Section: Targeting Chemosensory Ion Channels To Improve Swallowingmentioning
confidence: 99%